1998
DOI: 10.1007/s00585-998-0828-9
|View full text |Cite
|
Sign up to set email alerts
|

The summertime 12-h wind oscillation with zonal wavenumber <i>s</i> = 1 in the lower thermosphere over the South Pole

Abstract: Abstract. Meteor radar measurements of winds near 95 km in four azimuth directions from the geographic South Pole are analyzed to reveal characteristics of the 12-h oscillation with zonal wavenumber one s 1. The wind measurements are con®ned to the periods from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
107
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(118 citation statements)
references
References 24 publications
9
107
2
Order By: Relevance
“…Early results from our observations over the South Pole have con®rmed the existence of a 12 h oscillation Portnyagin et al, 1997b) which was ®rst observed by Collins et al (1992) in sodium densitȳ uctuations and then by Hernandez et al (1993) in the meridional wind ®eld. Additionally, a strong divergence event in April 1996 was observed and presented in Portnyagin et al (1997a).…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…Early results from our observations over the South Pole have con®rmed the existence of a 12 h oscillation Portnyagin et al, 1997b) which was ®rst observed by Collins et al (1992) in sodium densitȳ uctuations and then by Hernandez et al (1993) in the meridional wind ®eld. Additionally, a strong divergence event in April 1996 was observed and presented in Portnyagin et al (1997a).…”
Section: Introductionsupporting
confidence: 51%
“…2 is a strong 12 h (2 cycles/day) oscillation during the summer months from October through February which wanes during the winter months (Portnyagin et al, 1997b). Also present is a strong 24 h oscillation with the same type of seasonal behavior as the 12 h oscillation.…”
Section: Wave Spectramentioning
confidence: 93%
See 2 more Smart Citations
“…The installation of a meteor radar at the South Pole and its successful operation without interruption during two observational campaigns; January 19, 1995±Janu-ary 26, 1996, and November 21, 1996±January 27, 1997, provided unique opportunities for investigation of a broad spectrum of waves in the wind ®eld in the lower thermosphere over the South Pole for di erent seasons (Forbes et al, 1995;Portnyagin et al, 1996;Portnyagin et al, 1997Portnyagin et al, , 1998Palo et al, 1998). In these papers the main features in the seasonal behavior of the di erent wind oscillations at an average height of 95 km over the South Pole with characteristic periods equal to or greater than 12 h are discussed in detail.…”
Section: Introductionmentioning
confidence: 99%